Reporte de caso: carcinoma de células basales de la próstata. Tumor maligno infrecuente que puede simular cuadro clínico de hiperplasia prostática - Gallegos M., Iván; Miranda T., Rubén; Fernández F., Cristina; Valdevenito S., Juan Pablo (Revista Hospital Clínico Universidad de Chile, 2010)
The basal cell carcinoma of the prostate is a rare tumor. It usually presents as an obstruction to urine flow, mimicking prostatic hyperplasia with low or normal PSA. We report a 76 years old man with irritative and obstructive urinary symptoms, enlarged soft prostate and normal PSA level. A transurethral resection of prostate was performed. The histological analysis revealed a large tumor, with growth in nests of basaloid cells with minimal cytological atypia and low mitotic count. An infiltrative growth pattern and concentric perineural invasion were identified. The immunohistochemical study showed positivity for high molecular weight cytokeratin (clone 34BE12), p63, bcl-2 and C-erbB-2 oncoprotein. There was a weak reaction for cytokeratin 7, S100 and negative for PSA antibody. The Ki 67 proliferation index was 30%. The patient subsequently underwent a radical prostatectomy, which showed no extraprostatic extension or metastasis to lymph nodes.